Property attributes influencing profitability before and after conversion of vacant long-term rentals to short-term rentals - Kentaro Murota; Yangcheng Gu; Xiaorui Wang; Daisuke Matsushita (PLoS ONE, 2025)
In Japan, the growing number of vacant housing units has become a pressing issue, and an increase in inbound tourism has led to accommodation shortages and rising lodging prices. Converting long-term rentals (LTRs) into short-term rentals (STRs) has emerged as a practical solution; however, empirical evidence on which property attributes are best suited for such conversions remains limited. This study identified the physical and locational attributes of vacant LTRs in Tokyo’s 23 wards, which contributed to improved profitability following conversion. Using an open dataset of 7,772 Airbnb listings from 2024, we developed a hedonic pricing model to estimate rates based on floor area, distance to the nearest station, station ridership, nearby tourist attractions, and administrative districts. The model was applied to 20 930 LTR properties to estimate the profit ratio before and after conversion and identify favorable attributes. Higher STR profitability was linked to lower pre-conversion rent, proximity to high-ridership stations, and locations near many tourist attractions within 10 km, especially in wards near transport hubs (e.g., Setagaya, Shibuya, Meguro, Shinagawa, and Shinjuku) and in well-connected, lower-rent peripheral wards (e.g., Nakano and Suginami). These findings offer insights into housing stock utilization and provide guidance for STR regulations and tourism policies.